Expression of Cyclin D1 protein in residual tumor after neoadjuvant chemotherapy for breast cancer - Villegas, Sonia Lorena; Marmé, Frederik (Breast cancer research and treatment, 2018)
PurposeHormone receptor (HR)-positive breast cancer (BC) shows a poor response to neoadjuvant chemotherapy (NACT). New treatment targets like the Cyclin D1-CDK4/CDK6 complex are promising adjuvant/post-neoadjuvant therapeutic strategies. Evaluating Cyclin D1 overexpression in residual tumor could recognize those patients that benefit most from such post-neoadjuvant treatment. In this study, we determined Cyclin D1 expression in residual BC after NACT. Secondary aims were to correlate Cyclin D1 expression levels with clinicopathological parameters and to assess its prognostic value after NACT.MethodsWe retrospectively assessed the nuclear expression of Cyclin D1 on tissue microarrays with residual tumor from 284 patients treated in the neoadjuvant GeparTrio (n = 186) and GeparQuattro (n = 98) trials. Evaluation was performed with a standardized immunoreactive score (IRS) after selecting a cut-off value.ResultsA high expression level (IRS ≥ 6) of Cyclin D1 was found in 37.3% of the assessed specimens. An increased Cyclin D1 expression was observed in HR-positive tumors, compared to HR-negative tumors (p = 0.02). Low Cyclin D1 levels correlated with clinical tumor stage 1-3 (p = 0.03). Among patients with HR-positive/Her2-negative tumors and high Cyclin D1 expression, a better disease-free survival (DFS) was graphically suggested, but not significant (p = 0.21).ConclusionOur study demonstrates a measurable nuclear expression of Cyclin D1 in post-neoadjuvant residual tumor tissue of HR-positive BC. Cyclin D1 expression was not prognostic for DFS after NACT. Our results and defined cut-off suggest that the marker can be used to stratify tumors according to protein expression levels. Based on this, a prospective evaluation is currently performed in the ongoing Penelope-B trial.
Published online: 25 November 2017
Gesehen am 13.09.2018